Giving Flesh to Culture: An Enactivist Interpretation of Haslanger. Issue 1 (2nd January 2019) - Higgins, Joseph
ABSTRACT: Haslanger's rich framework for explaining sociality and ideological oppression is scaffolded by Zawidzki's [2013] notion of mindshaping . Through mindshaping—that is, the process of agents being moulded by cultures so as to have similar attitudes in response to certain stimuli—humans are channelled towards specific social practices, which generate social structures. Mindshaping thus configures human interactions in such a way that others' interactions are communally interpretable. While Haslanger is correct to highlight the canalising processes of social structures, her use of mindshaping paints a picture of humans as passive agents with respect to pre-existing cultural schemata. However, if one replaces the place of mindshaping as an underlying explanatory framework for cognition with the theory of enactivism, one can avoid theoretical lacunae, preserving the importance of active agency and lived experience.